Perkembangan Tingkat Pengembalian Investasi Pendidikan Menengah di Indonesia Tahun 2015 dan 2018 - Amalia, Nuelda; Sugiharti, Lilik (UI Scholars Hub, 2020)
This research aims to estimate returns to secondary education in Indonesia, especially senior and vocational high school, and its development in 2015 and 2018. Data from Indonesia National Labor Force Survey (NFLS) 2015 and 2018 are used here. Returns are estimated using Two-Step Heckman Method. The results are, in 2015, returns to senior high school (9,32%) are higher than vocational high school (8,89%). However, in 2018, returns to vocational high school (9,53%) are higher than senior high school (9,41%). This shift is caused by the increasing number of vocational school graduates absorbed in workforce and increasing income of vocational school workforce.